(untitled) (ModaPalavra e-periódico, 2026)
This work investigates the relationships between fashion, technique, and philosophical thought, based on the development of an authorial collection composed of twenty looks, divided into four conceptual families, inspired by the work of Michel Foucault. The objective of this article is to present the development of this collection and to reflect on how fashion, as a language and technical practice, can incorporate theoretical and conceptual discourses, in this case, regarding Foucault’s concepts of power, control, panopticism, discipline, subjectivity, resistance, truth, and parrhesia. This is possibly the first authorial fashion collection to use Michel Foucault’s work as a conceptual and aesthetic axis, proposing an unprecedented dialogue between Foucaultian thought and creative processes in the fashion field. The methodology adopted follows the principles proposed by Doris Treptow for the development of fashion collections, combining trend research, target audience definition, color palette, material selection, and garment construction. The analyses were conducted using photographs of the looks created, allowing us to observe how Foucaultian concepts were translated into form, texture, and modeling using fashion techniques. The results indicate that fashion can act as a critical and expressive medium, capable of destabilizing social conventions, fostering the emergence of new subjectivities, and engendering aesthetic experiences committed to thought. Thus, the study contributes to expanding the possible connections between theory and practice, inserting fashion creation into the realm of conceptual elaborations and debates about the techniques that constitute it.